The The Visibility of Disabilities within Pharmacy Program Recruitment Material - Farhat Hussain; Alesha Smith; Kyle Wilby (University of Minnesota Libraries Publishing, 2020)
Background: Targeted recruitment of students with disabilities is a novel area in pharmacy education and may help to attract qualified students in light of decreasing applicant numbers. The aim of this study was to explore the visibility of disabilities within online recruitment material for pharmacy programs and to determine the location of targeted information available to prospective students with disabilities. Methods: The top 50 ranked programs offering a professional pharmacy degree under the Pharmacy and Pharmacology QS subject rankings were identified and included if recruitment material was published in English. Online recruitment material was reviewed for presence of persons with disabilities in photos, presence or description of persons with disabilities in videos, information specific to disabilities on the program website (e.g. technical standards), and information specific to disabilities on the university website (if not located on the program website). Results: A total of 41 international program websites met the inclusion criteria. No programs included pictures or videos featuring persons with disabilities. A total of 18 (44%) of programs had disability information on the program website and an additional 18 (44%) of programs included information on the university website. There were 5 (12%) of programs that did not include any information about disabilities on the program or university website. Conclusion:  Recruitment material for pharmacy degree programs should be current, inclusive, and reflective of student populations eligible to be admitted. This study found a distinct underrepresentation of students with disabilities and information pertaining to disabilities within recruitment material for a sample of international pharmacy programs.   Article Type: Original Research